Effect of forage legumes intercropping on growth, yield and economics of sabaigrass (Eulaliopsis binata) - MOHAPATRA, S; TRIPATHY, S K; PATRA, A K (The Indian Journal of Agricultural Sciences, 2014)
An experiment was carried out during 1996-98 to evaluate the production potential and economic returns of sabaigrass [Eulaliopsis binata (Retz.) C E Hubb.]-based intercropping systems on rainfed upland of Similipal foot hills of Orissa. intercropping of forage legumes like mothbean [Vigna aconitiflius (Jacq.) Marcchal], stylos [Stylosanthes hanata (L.) Taubert.], cowpea [Vigna unguiculata (L.) Walp.], butterfly-pea [Clitoria ternatea L.], cluster bean [Cyamopsis tetragonolaba (L.) Taub.] and rice-bean [Vigna umbellata (Thunb.) Ohwi and Ohashi] was better than sole sabaigrass both in terms of total production and net return. Sabaigrass + sty los recorded highest sabaigrass equivalent yield (5.98 tonnes/ha), net return (Rs 7 626/ha) and benefit: cost ratio (2.78) followed by sabaigrass + cowpea (5.39 tannes/ha, Rs 6 689/ha, 2.67).